Branding of B-Schools by Understanding the Expectations of Their Three Major Stakeholders - Tigga, Amar Eron; Pathak, Pramod; Kumar, Rohit Vishal (Indian Journal of Marketing, 2014)
The branding of B-schools has become an important concern for the business education leaders as it communicates about the quality of their offerings, faculties, students, placements, financial resources, and so forth. Also, B-schools are facing cut-throat competition within and across different categories of business education providers. In such a situation, the proper positioning and development of right branding strategies for a B-school are a must. It would be possible to create the right branding strategies for a B-school by understanding the expectations of its stakeholders. The purpose of this study was to understand the expectations of major stakeholders, that is, students, recruiters, and faculty members of B-schools operating at three different levels, that is, premier, national, and regional levels. The study was carried out in 10 B-schools located in Jharkhand state, and data were collected from a sample of 334 students, 48 faculty members, and 34 recruiters. The findings showed that good placement opportunities were the most important expectation of students across the different levels of B-school students. There was a significant positive correlation between the expectations of students of national and regional level B-schools, but in case of faculty members, there was a significant positive correlation between the faculty members of national and premier level B-schools. Recruiters looked for the right attitude and students' ability to adapt to the organizational culture as compared to knowledge or skills. The findings of the study have significant implications for B-school branding. The study suggested that the B-schools must align their strategies and resources to deliver as per their stakeholders' expectations - especially as per the expectations of their students, recruiters, and faculties - to achieve a strong and successful brand image.